SELENIUM IN BIOLOGICAL FLUIDS IN THE BODIES OF PATIENTS WITH ASSOCIATED TRAUMA - Vasiuk V. Le.; Kovalchuk P. Ye.; Tulyulyuk S. V.; Shutka V. J. (World Science, 2019)
Modern literature widely covers the role of selenium and necessity of its intake in case of different diseases, but the studies concerning the dynamics of concentration of this element in patients with injuries of the muscular- skeletal system (MSS) and cranial-cerebral injuries (CCI) are isolated. At the same time, investigation of selenium metabolism in case of injuries of the MSS and CCI and development of the correction schemes are generally known to enable to improve the results of treatment considerably and decrease the consequences of injuries. Objective: to investigate the concentration of selenium in biological fluids in patients with associate trauma. Materials and methods: 42 patients, treated at the Traumatological Department for adults and Neurosurgical Department of the Emergency Rescue Hospital in Chernivtsi, were examined. All the patients were distributed into 3 groups: І group – patients with severe CCI and injuries of the MSS requiring vital activity support; ІІ group – with moderate CCI and injuries of the MSS; ІІІ (control group) – with injuries of MSS only. Results: The data obtained are indicative of decreased selenium concentration in all the biological media of the body (plasma, erythrocytes, urine) during the whole post-traumatic period, both in patients with severe CCI and injuries of the MSS and those with a moderate degree. Conclusions: 1. Pronounced disorders of selenium metabolism are evidenced to occur in patients with severe CCI and MSS injuries, which are manifested by its decreased concentration in all the examined biological media of the body during the whole acute period of injury. 2. The lack of considerable differences in selenium concentration in patients with severe CCI and MSS injuries and with moderate injuries is indicative of non- specificity of the disorders found, since they are a typical pathologic process peculiar for traumatic injury of any genesis and localization. 3. The state of selenium metabolism does not possess correlations with other clinical and biochemical laboratory indices. 4. Selenium deficiency requires administration of pharmacological correction, for example, with Selenase which is essential both in acute and post-traumatic periods.